Challenges of in vitro propagation and antimicrobial susceptibility testing of Mycoplasma genitalium. (18th August 2022) - Pitt, Rachel; Boampong, Dolcibella; Day, Michaela; Jensen, Jorgen Skov; Cole, Michelle
Abstract: The sexually transmitted bacterial pathogen Mycoplasma genitalium has proved a complex organism to work with in the laboratory setting. Exhibiting an extremely fastidious nature, successful in vitro propagation of M. genitalium has remained elusive for many researchers. Antimicrobial resistance to both first- and second-line recommended therapies (macrolides and fluoroquinolones, respectively) is commonly reported. However, phenotypic susceptibility testing is not routinely performed, due to the difficulties of in vitro growth. Instead, molecular detection of known resistance determinants is used to infer susceptibility/resistance. However, associations between determinant detection and clinical treatment failure are not always clear. Furthermore, molecular assays have limited use for detection of emerging resistance mechanisms. The present review collates and discusses the development of successful culture systems for initial isolation of this organism and current methodologies employed for phenotypic susceptibility testing to aid researchers in this field. As with Neisseria gonorrhoeae, future treatment options are extremely limited for M. genitalium and, if this sexually transmitted infection is to remain treatable, phenotypic susceptibility testing will play an invaluable role in evaluation of potential therapeutics. As such, retainment of these techniques is imperative.